Педагогическое мастерство преподавателей – фундамент формирования культуры нации - Долгарев, Анатолий Васильевич (НТУ "ХПИ", 2015)
В статье анализируется педагогический опыт проведения занятий с целью активизации познавательной деятельности учащихся, необходимой для формирования умения самостоятельно мыслить и выражать собственные суждения о процессах общественной жизни. Научным интересом автора данной статьи также стала проблема формирования творческого самостоятельного мышления у студентов ВУЗов. Особое внимание уделяется вопросу самостоятельного поиска решений проблемных ситуаций с целью развития у учащихся чувство ответственности, повышения интереса к теме и предмету обучения, а так же укрепление их волевых качеств. Освещаются главные цели проблемного обучения, в первую очередь таких как интеллектуальное и творческое развитие учащихся, а также овладения их знаниями, навыками, умениями и способами познания.

The article examines the educational experience of employment with a view to enhance the cognitive activity of pupils required to form the ability to think independently and express their own judgments about the processes of social life. Scientific interests of the author of this article also became a problem of formation of creative independent thinking in students of universities. Particular attention is paid to the independent search for solutions to problem situations to develop in students a sense of responsibility, to raise interest in the subject and object of study, as well as strengthening their willpower. Highlights the main objectives of problem-based learning in the first place such as the intellectual and creative development of students as well as their mastery of the knowledge, skills, abilities and ways of knowing.
Pedagogical skill of teachers - the foundation of building a culture of nation
Keywords: процесс обучения; познавательная деятельность; проблемное обучение; система методов; learning process; cognitive activity; problem teaching; system of methods; pedagogical skill